Study on wind-induced response of a large-span roof by using finite particle method. (December 2021) - Wang, Qinhua; Liu, Feihong; Yu, Ying
Abstract: The wind-induced response analysis of large-span roof using finite particle method (FPM) is discussed in this paper. Based on vector mechanics, FPM is an intrinsic method to study responses of structures under dynamic excitation. It adopts separated particles that governed by Newton's second law to describe structural behaviors, especially geometric nonlinearity. As the previous damping treatments in FPM are inadequate for studying the wind-induced responses of large-san roof, two enhanced treatments based on Rayleigh damping for approximatively estimating damping forces in the FPM are proposed and are verified through numerical pseudo-dynamic example. To study the wind-induced responses of a large-span roof, the wind-tunnel tests of pressure measurement are carried out to obtain time histories of wind loads on the large-span roof. The FPM is further employed to estimate wind-induced responses of the large-span roof. Wind-induced displacement and internal forces responses obtained by FPM are compared with results from finite element method (FEM). The results from FPM meet well with results from the FEM, which presents the capability of FPM to study the wind-induced responses of large-span roof.